Video chatting for seniors in easy steps - Vandome, Nick (In easy steps., 2021)
Video Chatting for Seniors enables readers to fully embrace the world of video chatting--including Zoom, FaceTime, Skype, and Facebook Messenger. Written with the senior reader in mind and presented in larger type for easier reading.